2014
DOI: 10.1177/1541931214581433
|View full text |Cite
|
Sign up to set email alerts
|

Automation and Inattentional Blindness in a Simulated Flight Task

Abstract: The study reported herein is a subset of a larger investigation on the role of automation in the context of single pilot aviation operations. This portion of the study focused on the relationship between automation and inattentional blindness (IB) occurrences for a runway incursion. The runway incursion critical stimulus was directly relevant to primary task performance. Participants performed the final five minutes of a landing scenario in one of three automation conditions (autopilot, autothrottle, and manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…In a simulated driving task conducted by Kennedy and Bliss (2013), participants who reported low mental demand while following automated navigational directives were more likely to experience IB to a task-relevant critical stimulus than those participants who reported higher mental demand. In part one of this study, participants monitoring flight automation were just as likely to exhibit IB to a critical stimulus as those flying manually (Kennedy et al, 2014). IB occurrence rates exhibited during automationinduced underload were equivalent to those exhibited during high workload, in line with the extended-U model of stress and performance (Hancock & Warm, 1989;Kennedy & Bliss, 2013).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…In a simulated driving task conducted by Kennedy and Bliss (2013), participants who reported low mental demand while following automated navigational directives were more likely to experience IB to a task-relevant critical stimulus than those participants who reported higher mental demand. In part one of this study, participants monitoring flight automation were just as likely to exhibit IB to a critical stimulus as those flying manually (Kennedy et al, 2014). IB occurrence rates exhibited during automationinduced underload were equivalent to those exhibited during high workload, in line with the extended-U model of stress and performance (Hancock & Warm, 1989;Kennedy & Bliss, 2013).…”
Section: Introductionsupporting
confidence: 53%
“…A large human-in-the-loop experiment was conducted in three stages to evaluate IB in an aviation context. The first run explored if low workload conditions found in highly automated environments could produce an IB occurrence rates similar to those observed during high workload conditions (Kennedy, Stephens, Williams, & Schutte, 2014). The second run attempted a second IB induction with a highly taskrelevant critical stimulus to explore IB rates and detection group memberships changes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of aviation safety on automation complacency (Parasuraman and Manzey, 2010) have shown that inattentional blindness (Simmons and Chabris, 1999) can be created by a warning device when shifting from monitoring an assisting device to performing a task (Bailey and Scerbo, 2007). In simulated flight pilots fail to detect a clear stimulus when target stimulus is unexpected and incomplete or incorrect representations of the situation are given by the warning device (Kennedy et al, 2014).…”
Section: Expectancy and Take-over Control In Brake Reaction Timesmentioning
confidence: 99%